THE EFFECT OF DIFFERENT CONCENTRATION OF TRIGARD, SEED TREATMENT METHOD AND REARING TEMPERATURE ON BIOLOGICAL ACTIVITY OF Callosobruchus maculatus (Fab.) REARED ON CHICKPEA - Nazar M. Al-Mallah (Mesopotamia Journal of Agriculture)
The results of the study revealed that the interaction between Trigard 75% W.P. concentrations, treatment methods and insect rearing temperatures on Callosobruchus maculatus reared on chickpea Cicer arietinum (L.) exhibit a varied effect on the rate of insect increase and dipping the chickpea seeds for one minute in a solution of Trigard 5% at 30 C, reduce the average of increase rate to 1.37 in comparison with control which reached 34.73. The effect of interaction between Tigard concentration, treatment methods and insect rearing temperature on the average of food consumption and the average generation period for two generations showed that increasing Trigard concentrations coincide with the reducing in the average weight loss of food of chickpea. Dipping the chickpea seeds in Trigard solution protect the seeds from insect attack in comparison with seed sprayed by Trigard and increasing the Tigard concentration increased the average generation period 34.17 day which was obtained from seed sprayed by 5% Trigard at 25 C. The studied factors showed no effect on sex ratio while it showed a significant difference for the weight between males and females.